Prevalence and risk factors of latent tuberculosis infection among college students: a systematic review and meta-analysis. (December 2022) - Yuan, Yemin; Wang, Xiyuan; Zhou, Yanxin; Zhou, Chengchao; Li, Shixue
Abstract: Objectives: College students are at increased risk of tuberculosis (TB), which increases their likelihood of developing latent tuberculosis infections (LTBI). This study aimed to estimate the pooled prevalence of LTBI and identify its risk factors. Study design: Systematic review and meta-analysis. Methods: We searched PubMed, Embase, Scopus, Web of Science, CNKI, Wanfang and CBM databases (10 March 2022) for studies published in any language. The pooled prevalence of LTBI was estimated using random effects methods. Factors associated with LTBI were evaluated by determining standardised mean difference (SMD) with 95% confidence interval (CI). All analyses were performed using the Stata 15.1. Results: A total of 50 studies from 18 countries were included, with 44 tuberculin skin test (n = 623, 732) and 19 interferon gamma release assay (n = 38, 266) estimates. The prevalence of a positive tuberculin skin test was 20% (95% CI: 17–23%), and the prevalence of a positive interferon gamma release assay was 9% (95% CI: 7%–11%) among college students. Older age (SMD: 1.67, 95% CI: 1.31–2.13), no Bacillus Calmette-Guérin vaccination/scar (SMD: 1.51, 95% CI: 1.06–2.16), contact with TB cases (SMD: 1.34, 95% CI: 1.11–1.62), clinical training (SMD: 1.93, 95% CI: 1.65–2.26) and overweight/obesity (SMD: 1.17, 95% CI: 1.06–1.30) were associated with a higher prevalence of LTBI. Sex was not associated with LTBI prevalence. Conclusion: College students have an increased risk of LTBI, although it varies by geographical area. This meta-analysis provides evidence of risk factors for LTBI in college students. Infection control measures should be conducted for college students with LTBI.